ASUHAN KEBIDANAN PADA NEONATUS NY. “S” DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Ariska, Wika; Astuti, Haryati; Madinah, Madinah (STIKES HUSADA GEMILANG, 2022)
Neonatal are the first period of life outside the womb until the age of 28 days. The infant mortality rate (Kemenkes, 2018) in Indonesia is 185/day, AKN 15 per 1000 live births. Based on the Dinkes Profile (2019), the number of neonatal deaths in Indragiri Hilir Regency is 21 neonatal deaths and a complete KN of 79.9% means that it has not reached the SPM target. This obstetric care is to provide care for Mrs.